Incidence of Complication of Ectropion and Entropion in Transconjunctival and Subciliary Approach for Treatment of ZMC Fracture - Muhammad Ahsan Bhatti, Erum Riaz, Afifa Razi, Sufyan Ahmed, Faiza Ahsan Rutaba Nadeem (Pakistan Journal of Medical & Health Sciences, 2023)
Objectives: The purpose of the study was to assess the frequencies of problems associated with ectropion and entropion whether the subciliary or transconjunctival technique is employed to repair ZMC fractures. Methodology: 50 patients with ZMC fractures who underwent surgical treatment in Abbottabad’s Ayub Medical College and Teaching Hospitals in 2021–2022 were included in this prospective hospital-based research. Pure ZMC Fractures were required for inclusion, while prior lid laxity, prevalence of trauma-related lid abnormalities, and pan face fractures were required for exclusion. Results: 50 patients in all were engaged over the study’s time frame; 28 patients received surgery using the sub ciliary route, with a mean delay of 11.25 days amongst the trauma & the operation, & 22 patients’ used the trans conjunctival method, with a mean delay of 30.60 days. Twelve of the patients with ectropion were men and two were women. Men made up both of the entropion patients. Male patients made up more of the sub ciliary approach group (82%, 22/28) than female patients (18%, 6/28). 14% of patients (3/22) in the transconjunctival approach group were female, whereas 97% (19/22) were male. The gender distribution of the patients in the two clusters did not vary statistically significantly (p=0.12). Conclusion: In terms of postoperative issues like entropion and ectropion, the study’s findings revealed that there is no discernible variance amongst the transconjunctival technique and the subciliary technique. It was challenging to draw any conclusions from this study’s findings due to the time and patient constraints. Hence, it is advised to repeat the study with a bigger sample size in mandate to obtain more reliable results. Keywords: Transconjunctival approach, Subciliary approach, Road traffic accident (Rta)